Caracterización morfológica de ecotipos nativos de chirimoya (Annona cherimola Mill.) con potencial agronómico en el cantón Espíndola, provincia de Loja - Ochoa Maldonado, Eddy Ramiro (2024)
Cherimoya is an exotic fruit native to the south of Ecuador, with very commercial physicochemical characteristics and great agronomic potential. This research is focused on studying the morphological diversity and identifying native individuals of cherimoya (Annona cherimola Mill.) with agronomic potential from the Espindola canton, of Loja province, in order to promote the production, conservation or improvement of this species. The study was developed through in situ sampling, where 54 cherimoya trees were characterized and 34 morphological and agronomic variables of interest were recorded in the plant, leaves, flowers and fruits, including qualitative and quantitative variables. The data collected were analyzed using statistical methods and multivariate analysis, which allowed the identification of patterns of morphological variation among the different cherimoya ecotypes, a wide morphological diversity was found among the samples collected, suggesting the presence of a great genetic variability. In addition to the morphological characterization, fruit quality analyses were carried out, evaluating aspects such as seed content in 100 g of pulp, soluble solids, acidity and firmness of the exocarp. These analyses allowed finding four accessions with fruits that meet parameters of excellent quality, similar to commercial varieties, which will allow valuing and properly exploiting the genetic resources present in this area, promoting their conservation and possible use in genetic improvement programs. In addition, this research will contribute to scientific knowledge about cherimoya diversity and better cultivation strategies, which will benefit local farmers and the economy of the region.